ANALISIS REVENUE SHENANIGANS PADA PERUSAHAAN PT GARUDA INDONESIA (PERSERO) Tbk - Junnestine Junnestine; Natalis Christian (FKIP, Universitas Banten Jaya, 2021)
Revenue shenanigans was actions that present false financial statements or manipulated reports with several techniques was included recorded income at the beginning, recorded fake income, diverted income to the next period. This study utilized a qualitative approach in explaining the phenomena that occured in detail and the source of the data used was secondary data. The purpose of this paper was to analyze the revenue shenanigans that had been violated by PT Garuda Indonesia Tbk. The result of this study proved that PT Garuda Indonesia Tbk had made the 1st revenue shenanigans in manipulating its financial statements.